Perceived Experiences of Families of Children with Unilateral Cerebral Palsy in the Implementation of a Task-Specific Intervention in the Home Environment with an Upper Limb Splint: A Qualitative Study - Patricia Roldán-Pérez; Vanesa Abuín-Porras; Isabel Rodríguez-Costa; María Ortiz-Lucas; Pablo Bellosta-López; Almudena Buesa-Estéllez (MDPI AG, 2024)
Introduction: Specific home tasks and the use of splints seem to positively affect altered structures and functions, as well as the activities and participation, of children with unilateral cerebral palsy (UCP). However, how did families experience the implementation of these therapies? Objective: To describe the experiences as they were perceived by the families of children with UCP before, during, and after a specific task intervention in the home environment, either with or without upper limb splinting. Methods: A qualitative, descriptive, phenomenological study was conducted in a natural environment. Fourteen families caring for children with UCP who participated in a previous randomized controlled trial were included. Data from unstructured and semi-structured interviews were analyzed through a thematic analysis. Results: Fourteen families (17 parents, age 37-47 years) caring for children with UCP (14 children, ages 6-10 years, 64% female) were interviewed. The following three themes emerged: "The project itself", in which families explained that they enrolled because of their trust in therapists; "Results obtained", where the main improvement was the integration of the assisting hand in the body schema; and "Lights and shadows", where families showed what they learned as positive points and some negative aspects related to the assessments and splints. Conclusions: The perceptions of the parents after the specific task intervention in the home environment showed a greater integration of the most affected side. Nevertheless, although the support of a splint on the hand can have beneficial results in terms of performance, other drawbacks leading to the disuse of the splint were highlighted.